Selected elements of motivational impact on sport performance in professional volleyball teams - Seweryniak, Tomasz; Nowak, Agnieszka; Stosik, Aneta (Quality in Sport, 2016)
The purpose of this study is to present techniques and means through which professional sport teams coaches may influence their players’ motivation. It includes analysis of present solutions used in practice and indicates directions for potential improvements. The conclusions of this study are based on a series of dedicated survey concerning various elements of motivational impact. The research was carried out among  polish coaches of professional men’s volleyball league. The studies of literature combined with practical experience, allowed the authors to present a set of elements of motivational impact, including motivating methods referring to different sources and forms of motivation. The results show that in the process of motivation coaches resort to both individual and collective techniques of influence. Motivational means declared to be used by respondents include: motivational speech, ongoing assessment of actions, raising voice,  using reward and punishment system,  code of honor and motivational recordings with own and opponent’s actions.